DEVELOPMENT OF TEXT WORKING SKILLS IN RUSSIAN LANGUAGE LESSONS - Orimbetova Laura (International Journal of Innovations in Engineering Research and Technology, 2023)
This article presents ideas about developing students' speech, listening comprehension, and reading comprehension skills by working on the text in Russian language classes.